Outcomes of Pregnancy After Bariatric Surgery. Issue 1 (March 2016) - Johansson, K.; Cnattingius, S.; Näslund, I.; Roos, N.; Lagerros, Y.T.; Granath, F.; Stephansson, O.; Neovius, M.
Abstract : ( N Engl J Med. 2015;372:814–824) Maternal obesity is a risk factor for gestational diabetes, with concordant increased risks of macrosomia, delivery complications, obesity in the offspring, stillbirth, preterm birth, and some congenital malformations. Small studies investigating the impact of prepregnancy bariatric surgery on gestational diabetes have yielded inconclusive results, and systematic reviews assessing the risk of neonatal complications after bariatric surgery have been limited due to study flaws, which include small sample sizes, heterogeneous study designs, and lack of matching for presurgery body mass index (BMI).